Influence of PEO/PMMA polymer electrolyte composition on charge transport and recombination dynamics in dye-sensitized solar cells (American Innovator: Journal of Emerging Technologies and Research, 2026)
Electrolyte composition plays a decisive role in governing ionic transport, interfacial charge transfer, and recombination dynamics in dye-sensitized solar cells (DSSCs). In this work, a series of polymerbased electrolytes with systematically varied PEO/PMMA ratios were prepared and investigated using electrochemical impedance spectroscopy (EIS) and intensity-modulated photocurrent/photovoltage spectroscopy (IMPS/IMVS). The influence of polymer matrix composition on ionic conductivity, recombination resistance, electron lifetime, diffusion coefficient, and charge collection efficiency was quantitatively evaluated. The results demonstrate that optimized PEO/PMMA ratios can effectively prolong electron lifetime while maintaining sufficient ionic conductivity. The findings provide a direct electrochemical basis for electrolyte engineering in advanced DSSCs.
Keywords: Dye-sensitized solar cells; Polymer electrolyte; Electrochemical impedance spectroscopy